The relationship between borderline personality disorder and bipolar disorder - Zimmerman, Mark (Les Laboratoires Servier, 2013)
It is clinically important to recognize both bipolar disorder and borderline personality disorder (BPD) in patients seeking treatment for depression, and it is important to distinguish between the two. Research considering whether BPD should be considered part of a bipolar spectrum reaches differing conclusions. We reviewed the most studied question on the relationship between BPD and bipolar disorder: their diagnostic concordance. Across studies, approximately 10% of patients with BPD had bipolar I disorder and another 10% had bipolar II disorder. Likewise, approximately 20% of bipolar II patients were diagnosed with BPD, though only 10% of bipolar I patients were diagnosed with BPD. While the comorbidity rates are substantial, each disorder is nontheless diagnosed in the absence of the other in the vast majority of cases (80% to 90%). In studies examining personality disorders broadly, other personality disorders were more commonly diagnosed in bipolar patients than was BPD. Likewise, the converse is also true: other axis I disorders such as major depression, substance abuse, and post-traumatic stress disorder are also more commonly diagnosed in patients with BPD than is bipolar disorder. These findings challenge the notion that BPD is part of the bipolar spectrum.